Entrepreneurial Self-Efficacy and Entrepreneurial Intention: The Mediating Role of Entrepreneurship Intentional Self-Regulation among Future Entrepreneurs - Cynthia Elitha; Debora Eflina Purba (Universitas Hayam Wuruk Perbanas, 2020)
Prior studies have explored the correlation between students' entrepreneurial self-efficacy and entrepreneurial intention. Several studies found a strong relationship between them, while others suggested a moderate or even weak correlation. This research aims to explore the mediating effect of entrepreneurship intentional self-regulation (EISR) on the relationship between entrepreneurial self-efficacy (ESE) and entrepreneurial intention (EI) among undergraduate students as the representative of future entrepreneurs in Indonesia. There is a need to explain this concept considering that the emergence of entrepreneurs is one of Indonesia's priorities. Data were collected from 299 undergraduate students in their final year of studies from eight universities, which provide entrepreneurship-based education in Jakarta and Bandung. Hayes’s PROCESS Macro in SPSS was used to analyze the effect. The results showed that entrepreneurship intentional self-regulation (EISR) was fully mediated the relationship between entrepreneurial self-efficacy and entrepreneurial intention among undergraduate students in Indonesia. This suggests that universities need to design curriculum and learning methods that encourage students' intention to become entrepreneurs.